Determination of Rare Earth Elements in Soil and Stream Sediment by Inductively Coupled Plasma-Mass Spectrometry with Automatic Graphite Digestion - Meiyun ZENG; Qisheng HE; Xin SHAO; Xiaoli YANG (Yankuang ceshi)
BACKGROUNDRare earth elements were used as geochemical tracers usually to provide important information for revealing the genesis of rocks and minerals, geochemical conditions of diagenesis and mineralization, material sources and magmatic differentiation and evolution, due to their stable chemical properties and high degree of uniformity. Therefore, it was very important to develop a method for rapidly and accurately determining the contents of rare earth elements in geological samples. In addition, due to the complex matrix of geological samples, most samples needed to be acid-dissolved in pre-treatment, and the amount of acid-dissolved reagents was large. The acid mist generated in the process of sample dissolution was harmful to the experimental personnel and the labor intensity of batch sample pretreatment was high.OBJECTIVESTo establish a rapid and accurate method for batch determination of rare earth elements in geological samples.METHODSA method was developed to measure 15 rare earth elements such as La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y in soil and stream sediment by inductively coupled plasma-mass spectrometry with Rh and Re as the internal standard, in which the pre-treatment process of “acid addition—digestion—acid removal—constant volume—shaking” was controlled by software and completed with an automatic graphite digestion instrument. The digestion procedure, the effects of digestion mixed acid, precision, accuracy, and detection limit of the method were studied by soil and stream sediment reference materials including GBW07402, GBW07446, GBW07448, GBW07454, GBW07456, GBW07457, GBW07304a, GBW07307a, GBW07308, GBW07312, GBW07359 and GBW07361.RESULTSThe results showed that the amount of mixed acids was 4mL consumed by soil and stream sediment digestion according to optimized digestion procedure. The absolute values of relative error and ΔlgC of rare earth elements were 0-6.67% and 0-0.028, respectively. Therefore, the measured values were consistent with certified values. The relative standard deviation (RSD) of rare earth elements was 0.97%-4.62%, which is lower than the RSD of the electric plate digestion method.CONCLUSIONSThe precision, accuracy and detection limit of the method meet the requirements of the specification of testing quality management for geological laboratories-part 4 “Analysis methods for regional geochemical sample”. The precision of the method is better than electric plate digestion method. The amount of mixed acid used in the method is 4mL, which is much lower than that in the electric plate digestion method, the corresponding environmental pollution is also reduced. The detection limit of most rare earth elements in the method is lower than that in the standard method. The pre-processing of the automatic digestion method only requires the experimental personnel to weigh the sample and place it in the digestion tube in the automatic graphite digestion instrument and the whole process of dissolution is then automated. The automation degree is high, which guarantees the safety of experimental personnel to the greatest extent and can be applied to the testing of batch samples.